ESENSI TATTWA PADA LONTAR KIDUNG SEBUN BANGKUNG - I Nyoman Temon Astawa; Ni Made Resi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Tattwa is the true teaching of the essence of Brahman (God) and everything related to God's omnipotence. God or Brahman is the origin of all that exists, Brahman is the primacosa whose existence is absolute. Because the source of all that exists, without Brahman it is impossible for everything to exist. Tattwa is the real and ultimate truth. This Tattwa as a philosophical concept is based on the goal to be achieved by that philosophy, namely the highest and essential truth. In the lontars in Bali, the word Tattwa is used more often when compared to the other three philosophical terms, education, holy places, yadnya ceremonies, customs and others, all of which are the basic concept or essence of which is Tattwa. Thus, tattwa is a philosophical term of religion which means the true and essential truth based on reflection that really requires brilliant thinking in order to arrive at the nature and nature of nature.